DINAMIKA AKSES PENGUASAAN TANAH, SISTEM USAHA TANI, DAN PILIHAN KOMODITAS: STUDI KASUS DI KAWASAN HUTAN GUNUNG KALEDONG - M. Gunardi Judawinata (Universitas Galuh, 2022)
This paper, departing from the results of preliminary research conducted since the end of 2020, using a political-ecological perspective will explain the dynamics of farmers to control land in areas that are included in the 'forest area' in Kawa-san Mount Kaledong ( West Java) and the dynamics of changing land use in the area – from tension to 'cooperation'. In addition, this paper will also explain the forms or patterns of farming/production systems that take place due to the development of the value of coffee commodities. The first proposition departs from the argument that the dynamics of access to tenure and land cultivation have consequences on production relations and social organization of production (planting system) where the choice of commodity is a determining factor in these dynamics. The second proposition is that coffee has a high economic value, although it opens up opportunities for farmers to cultivate a number of lands within the 'forest area', leaving farmers involved in farming without the freedom to manage all factors of production. So it can be said that they are not in a position as “independent farmers”, but only as small commodity producers, while the largest economic control lies with non-farmer actors.